Unidad de investigación del fruto de la palma de acai (2021)
The area to be intervened is in Colombia, in the department of Amazonas; where the first stage of intervention begins, in which the territory and its main particularities are analyzed. It starts from this for the realization of a master plan based on the recovery and revitalization of the fluvial connectivity through the Putumayo river and a port infrastructure, on the other hand, the integration of this area with the rest of the country is consolidated. of resources as a boost to the economy and new alternatives for production and use of the land, thus generating job offers for natives. Thus turning everything around biodiversity where crops, river resources, reforestation areas and native and ecological protection areas prevail, based on this a master plan is proposed in the village of Tarapacá, specifically in the urban area of ​​the village.